Development of an intervention model to prevent stunting in children in Batam - Nasution, Nurhafizah (Journal of Midwifery and Nursing, 2025)
Stunting remains a significant public health challenge in Indonesia, including in Batam City, which is characterized by rapid population growth and urbanization. This condition not only hampers children’s physical growth but also affects their cognitive development and long-term productivity. This study aims to design and implement a community-based intervention model for the prevention of stunting among children aged 0–59 months in Batam. A mixed methods design with an exploratory-sequential approach was employed. Qualitative data were collected through in-depth interviews with health workers, posyandu cadres, and parents, while quantitative data were obtained from questionnaires distributed to 150 mothers of toddlers. Data were analyzed descriptively and inferentially using correlation tests, logistic regression, and thematic triangulation. The findings revealed that the main determinants of stunting in Batam include mothers’ limited knowledge of nutrition and exclusive breastfeeding, substandard quality of complementary feeding, restricted access to health services, and poor environmental sanitation. In response, a community-based stunting prevention model was developed consisting of four integrated components: (1) nutrition education for mothers through kelas balita (toddler classes), (2) strengthening posyandu capacity through cadre training and provision of growth monitoring tools, (3) promotion of local food utilization in complementary feeding, and (4) multi-sector collaboration among health workers, local government, and community stakeholders. The study concludes that the proposed model effectively enhances mothers’ nutritional knowledge, improves child feeding practices, and fosters sustainable community participation in stunting prevention. This model provides a practically applicable framework that can be integrated into local public health programs as a sustainable and scalable strategy to accelerate stunting reduction in urban settings like Batam.